ПЕДАГОГІЧНА ДІАГНОСТИКА ЯК ЗАСІБ РОЗВИТКУ ТВОРЧИХ ЗДІБНОСТЕЙ МАЙБУТНІХ ВЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2007)
In article problems of pedagogical diagnostics, and influence on development of creative abilities of students are considered during training in the higher school.